2019
DOI: 10.1186/s43066-019-0015-6
|View full text |Cite
|
Sign up to set email alerts
|

S100A14 protein as diagnostic and prognostic marker in hepatocellular carcinoma

Abstract: Background: Protein S100A14 has recently been implicated in the progress of several types of cancers. This study aimed to investigate the clinical significance of S100A14 in the diagnosis of hepatocellular carcinoma (HCC). Results: S100A14 was significantly elevated in the HCC group. A cut-off value for serum S100A14 between the HCC group and cirrhosis group is > 0.47 with a sensitivity of 100% and specificity of 88.57%. S100A14 level was a significant diagnostic factor for HCC and a good reference for HCC pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…AFP concentration in the current study was significantly higher in HCC group when compared to CHCV and control groups, which was in same line with previous studies, found that elevated AFP levels are associated with higher pathological grade (21). AFP measurements showed a statistically significant difference between the studied groups, which increased in HCC in comparison to cirrhosis and the control group (22). The present study revealed that significant decrease in miRNA-23b gene expression level in HCC group when compared to CHCV and control groups.…”
Section: Discussion Discussionsupporting
confidence: 92%
“…AFP concentration in the current study was significantly higher in HCC group when compared to CHCV and control groups, which was in same line with previous studies, found that elevated AFP levels are associated with higher pathological grade (21). AFP measurements showed a statistically significant difference between the studied groups, which increased in HCC in comparison to cirrhosis and the control group (22). The present study revealed that significant decrease in miRNA-23b gene expression level in HCC group when compared to CHCV and control groups.…”
Section: Discussion Discussionsupporting
confidence: 92%
“…However, Li et al presented evidence showing that S100A4 in cooperation with collagen I is involved in the development of fibrosis-associated HCC by upregulating stem cell marker genes, for example, Oct-4, Nanog, and SOX2, via RAGE-dependent β-catenin signalling [197]. Recently, S100A14 was introduced as a promising marker, as it was overexpressed in HCC tissue compared with healthy liver tissue and cirrhosis tissue, and therefore might be a sensitive assistant for diagnosis of HCC [198,199].…”
Section: S100 Proteins In Other Cancer Typesmentioning
confidence: 99%
“…Many studies revealed that altering in S100A14 expression is associated with cancer progression and prognosis [10,18,19]. Previous studies have also clearly revealed the presence of S100A14 in serum as it is secreted by cancer cells and exerts extracellular functions [20,21]. Therefore, we aimed in this study to determine the levels of S100A14 protein in serum samples of breast cancer patients and healthy individuals.…”
Section: Discussionmentioning
confidence: 97%